Co-teaching Biology 1100 with Dr. Jason Gee - Hance, Jason T. (My University, 2014)
For my Senior Honors Project, I participated in co-teaching an Introductory Biology, or Biology 1100, class alongside department faculty member Dr. Jason Gee. My overall goals for this project were to better master the concepts of basic biological principles as set forth by the course material, as well as, to become experienced in the art of projecting what knowledge I had learned in the field of biology from myself to the students who attended introductory biology. I did so by creating an original PowerPoint lecture presentation that I would present to the students, as well as, created an Active Learning Exercise that corresponded to the lecture presentation and required that students actively apply the knowledge they had just learned. This paper reflects on the co-teaching experience as a whole and summarizes the main points that I learned to improve upon my experiences.
Keywords: Co-teaching; Biology 1100; Gee, Jason, Dr.